2013
DOI: 10.1590/s1516-35982013001100008
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile and composition of milk protein fraction in dairy cows fed long-chain unsaturated fatty acids during the transition period

Abstract: -The objective of this study was to evaluate the utilization of different sources of unsaturated long-chain fatty acids in diets for dairy cows during the transition period and early lactation on the milk fatty acid profile and composition of the protein fraction. Thirty-six Holstein cows were divided into three groups, fed the following diets: control (C); soybean oil (SO); and calcium salts of long-chain unsaturated fatty acids (CS). The milk samples utilized for analysis were obtained weekly from parturitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
2
5
0
3
Order By: Relevance
“…Similar results were observed for body weight (Table 3), data also present in (RENNÓ et al 2013) Interaction effect was significant for Fat corrected milk (FCM) (P<0.05) No difference was observed between the contrasts evaluated. Time effects were observed (P<0.05) for the dry matter intake, milk yield and energy balance (Figure 1).…”
Section: Resultssupporting
confidence: 83%
“…Similar results were observed for body weight (Table 3), data also present in (RENNÓ et al 2013) Interaction effect was significant for Fat corrected milk (FCM) (P<0.05) No difference was observed between the contrasts evaluated. Time effects were observed (P<0.05) for the dry matter intake, milk yield and energy balance (Figure 1).…”
Section: Resultssupporting
confidence: 83%
“…The inhibiting effect of unsaturated C18 on de-novo synthesis has been known in the past, but precise mechanisms involved in the studies were not yet well understood, even if some 18:2 isomers, such as C18:2 trans-10, cis-12, have been identified (Bauman and Griinari, 2001). Renno et al (2013) also found milk fat depression and short-chain fatty acid concentration decrease in dairy cows fed with long-chain unsaturated fatty acids. In the present study, soybean oil increased milk C18:2 cis-9 trans-11, C18:2 trans-10 cis-12 and decreased short and medium chain fatty acid concentration and chitosan was not able to inhibit linoleic acid biohydrogenation in fat supplemented diets.…”
Section: Tablementioning
confidence: 99%
“…16,75 15,82 0,3919 0,1155 C18:1 cis-11 0,65 0,62 0,0142 0,1803 C18:1 cis-12 0,33 0,27 0,0094 0,0003 C18:1 cis-13 0,061 0,056 0,0027 0,2582 C18:1 cis-14 0,076 0,079 0,0026 0,4124 C20:1 cis-11 0,096 0,094 0,0064 0,8665 AG C18:1 trans C18:1 trans-4 0,013 0,009 0,0007 0,0057 C18:1 trans-5 0,012 0,008 0,0012 0,0392 C18:1 trans-6 a trans-8 0,15 0,12 0,0051 0,0015 C18:1 trans-9 0,25 0,21 0,0064 0,0001 C18:1 trans-10 0,32 0,27 0,0117 0,0070 C18:1 trans-11 1,06 1,08 0,0456 0,7866 C18:1 trans-12 0,29 0,22 0,0076 <0,0001 C18:1 trans-13 e trans-14 0,42 0,33 0,0172 0,0020 C18:1 trans-16 0,27 0,21 0,0104 0,0015 Σ C18:1 trans 2,78 2,44 0,0807 0,0104 Isômeros conjugados (CLA) e não conjugados (NCLA) do ácido linoleico C18:2 trans-9 trans-12 (NCLA) 0,069 0,053 0,0036 0,0060 C18:2 cis-9 trans-12 (NCLA) 0,066 0,065 0,0040 0,8323 C18:2 trans-9 cis-12 (NCLA) 0,107 0,099 0,0039 0,2010 Σ NCLA 0,24 0,22 0,0103 0,1008 CLA cis-9 trans-11 0,58 0,53 0,0254 0,2310 CLA trans-9 cis-11 0,025 0,022 0,0043 0,7022 CLA trans-10 cis-12 0,014 0,015 0,0020 0,6387 AG de cadeia longa ω-6 e ω-3 C18:2 cis-9 cis-12 (ω-6) 1,82 1,66 0,0641 0,0951 γ-C18:3 cis-6 cis-9 cis-12 (ω-6) 0,024 0,023 0,0015 0,8156 C18:3 cis-9 cis-12 cis-15 (ω-3) 0,22 0,20 0,0077 0,1463 C20:2 cis-11 cis-14 (ω-6) 0,031 0,024 0,0030 0,1370 C20:3 cis-8 cis-11 cis-14 (ω-6) 0,076 0,086 0,0054 0,2139 Araquidônico (C20:4 cis-5 cis-8 cis-11 cis-14) (ω-6) 0,14 0,15 0,0086 0,8573 EPA (C20:5 cis-5 cis-8 cis-11 cis-14 cis-17) (ω-3) 0,044 0,051 0,0032 0,1425 DHA (C20:6 cis-4 cis-7 cis-10 cis-13 cis-16 cis-19) (ω-3) 0,060 0,068 0,0048 0,2385 Σ AG ω-6 cis 2,09 1,93 0,0703 0,1335 Σ AG ω-3 cis 0,32 0,32 0,0132 0,9532 Não houve efeito (P>0,05) da inclusão de GB sobre o teor do ácido esteárico no leite (Tab. 4), cujos valores são similares ao obtido (9,1g/100g de AG) em trabalho realizado no Brasil com vacas alimentadas com silagem de milho e concentrado não lipídico (Rennó et al, 2013). No entanto, os teores de ácido oleico (Tab.…”
Section: Resultsunclassified
“…No entanto, os teores de ácido oleico (Tab. 4) podem ser considerados baixos em relação aos relatados por Rennó et al (2013) Zootec., v.72, n.1, p.243-252, 2020 al., 2015) demonstraram que até ~11% de glicerol na MS da dieta em substituição ao amido não altera o pH, mas modifica a proporção molar de ácidos graxos voláteis no rúmen, com maior concentração de propionato às expensas de acetato.…”
Section: Resultsunclassified